HUBUNGAN KARAKTERISTIK INDIVIDU DAN PERILAKU PADA PETUGAS MANAJEMEN TERPADU BALITA SAKIT (MTBS) DENGAN CAKUPAN PENEMUAN PNEUMONIA DI PUSKESMAS KABUPATEN KEBUMEN - Patria Silviana; Retno Hestiningsih; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Pneumonia is an acute infection of the lung tissue (alveoli). The purpose of research is to know relation of individual characteristics and behavior in integrated management of childhood illness (IMCI) official to the coverage detection of pneumonia in Public Health Center in Kebumen Regency. Type of research is analytic observational with cross sectional approach. The population of research are all IMCI official in 35 Public Health Center in Kebumen Regency total number of 556 IMCI official and the number of samples is 93 samples use to the sampling technical is accidental sampling. Univariat analysis is table of frecuency distribution and narrative. Bivariate analysis use the chi-square test and kendall’s tau b test correlation. The result of research shows that respondents aged over ≥36 years (55,9%), female (95,7%), background in DIII obstetrics education (80,6%), long years of work (53,8%), good knowledge (75,3%), good attitude (61,3%), poor practice (53,8%), good perception of public health leadership supervision (64,5%), good perception of motivation (55,9%). There is one variable that related is good perception of public health leadership supervision (p=0,002). In while, there are eight variables that not related are official ages (p=0,105), sex (p=0,569), education (p=0,112), years of work (p=0,371), knowledge (p=0,378), attitude (p=0,457), practice (p=0,597) and good perception of motivation (p=0,258). Recommended to the Department of Health increase on the job training and to the Public Health Center more intensive in the implementation of supervision.